Prácticas profesionales en escenarios complejos - Vazquez, María Inés (2018)
This study focuses on the thoughts provided by students in their last year of a Bachelor degree at a university institution of Uruguay. The research is part of the professional skills that these young people put into action within the framework of the workshops of applied research offered during the last year of their career, in which they perform a diagnostic approach and a proposal for improving a practice center.The study lasted a total of eight months, during which various techniques were applied (online survey, focus groups, interviews and document analysis), aimed at students and key informants whose contributions allowed comparing points of view and supplementing information. It was sought at all times to articulate specific records of each experience with other global contributions from the multicase methodology in order to analyze the processes of change management. The document closes resuming the study objectives that seek to generate critical reflection on the professional practices put into action presenting the main findings achieved, in dialogue with theoretical contributions that guided the process of analysis.